Aberrant pulvinar effective connectivity in generalized social anxiety disorder. Issue 45 (November 2016) - Tadayonnejad, Reza; Klumpp, Heide; Ajilore, Olusola; Leow, Alex; Phan, Kinh Luan
Abstract : Abstract: Recent neuroimaging findings in general social anxiety disorder (gSAD) have extended our understanding of the neural mechanisms of gSAD beyond an amygdala-centric fear-based hyperactivity model to include other brain regions and networks relevant to salient cues. In particular, higher order areas compromising visual networks that process emotional and social information have been implicated. The pulvinar anchors this network and is a key regulatory node that mediates complex sensory inputs and the integration between limbic and frontal brain systems. However, the role of the pulvinar and specifically alteration of its effective connectivity with the rest of the brain has not been examined in the pathophysiology of gSAD, a disorder characterized by aberrant socio-emotional processing. The main aim of this study was to examine the pulvinar network effective connectivity in gSAD. In this study, we recruited 21 individuals with gSAD and 19 demographically matched healthy controls (HC), who performed an emotional face processing task while brain activity was recorded using functional magnetic resonance imaging (fMRI). To examine pulvinar-based network dynamics, Granger causality (GC) based effective connectivity (EC) analysis was applied on fMRI data to compare gSAD and HC. The EC analysis revealed heightened casual influential dynamics between pulvinar in higher order visual and frontal regions in gSAD. In conclusion, these preliminary data suggest a novel network-based cortico-pulvino-cortical neural mechanism in the pathophysiology of gSAD.